PERANCANGAN ALAT PENUKAR KALOR TIPE SHELL AND TUBE UNTUK GASOLINE ENGINE CM11-MKII - Christian Lasut; Benny L Maluegha; Frans Palobo Sappu (JURNAL POROS TEKNIK MESIN UNSRAT, 2022)
Shell and tube is one type of heat exchanger that serves to change the temperature of a fluid. To support the performance of this equipment, proper design and appropriate capcity are needed. The purpose of this research is to make a design of shell and tube heat exchanger on the gasoline engine CM11-MKII.The design of this shell and tube heat exchanger is done by using the Kern method. Kern’s calculation is easier to understand, as the sequence of calculations and formulas used are clearly displayed. The completion stage of the design still uses trial and error methods.The specifications obtained for the inner diameter of the shell are 8 inches with a baffle distance of 6 inches and the number of tracks is 2 tracks. While the specifications for the tube are 16 inches long, 0.584 inches inside diameter, 0.75 inches outside diameter and the number of tracks is 4 tracks.The calculation results using the above specifications obtain a total heat transfer coefficient of 401.71 Btu/hour.ft2. °F, while for the design coefficient of 205 Btu/hour.ft2.°F and the fouling factor that occurs is 0.0023 hours.ft2.°F . The calculations obtained meet the requirements of the shell and tube type APK with water as the working fluid.Keyword: Design, Heat Exchanger, Shell and tube